Stop playing safe : how to be braver in your work, leadership and life - Warrell, Margie (Ascent Audio, 2022)
Have you ever looked back and wished you'd been braver? If you ever hold back from making changes or taking chances, Stop Playing Safe is for you. In this fully updated "post-pandemic" edition, Dr. Margie Warrell challenges you to "rethink risk" and back your boldest goals with braver action. Drawing on her diverse global experience working in coaching, psychology, and with trailblazing leaders such as Richard Branson and Bill Marriott, this book will empower you to master fear and "take the chance" when it matters most. Margie will get to the heart of what's holding you back, giving you proven strategies to: find your "Why" to do more of what ignites your passion (and less of what doesn't!); uncover your blind spots to make smarter decisions, faster; apply four simple steps to build resilience and manage your "stress triggers"; activate "post traumatic growth" to turn your toughest problems into your greatest growth; nail difficult conversations to resolve conflict, build trust, and strengthen relationships; and be an inspiring leader who emboldens others to think bigger, learn faster, and accomplish more.